Project-Based Learning on Students’ Collaborative Skills and Learning Outcomes in Food and Beverage Service Course - Masdarini, Luh; Raka Marsiti, Cokorda Istri (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
The current study investigated the effect of project-based learning on students’ collaboration skills and learning outcomes in food and beverage services, particularly in restaurant customs. A quantitative approach was used in this study by adapting a posttest-only control group design. Eighty students took culinary arts concentration in the Family Welfare Education study program at Universitas Pendidikan Ganesha selected as the research sample. They were selected by using total random sampling. The data were collected through posttest and questionnaire distribution. The posttest was conducted to collect data on students’ learning outcomes; meanwhile, questionnaire distribution was purposed to obtain students’ collaboration skills. The research instruments were a questionnaire and a test. The data were analyzed quantitatively through descriptive and inferential statistical analysis. The inferential statistic analysis was conducted using the t-test and MANOVA with the assistance of SPSS 25. The results showed that 1) project-based learning significantly affected students’ collaboration skills, 2) project-based learning affected students’ learning outcomes, and 3) there was a significant simultaneous effect of collaboration skills and learning outcomes in the restaurant food and service course.